Bromfenac (Broksinak) — a new word in the nonsteroidal antiinflamatory drug (literature review) - E. A. Spiridonov (Oftalʹmologiâ, 2016)
Eye inflammation can be caused by different factors — allergies, infection, trauma (including surgery). It can have severe complications, last even after elimination the reason and cause the visual impairment as an outcome. Two main classes of anti-inflammatory agents (corticosteroids and nonsteroidal anti-inflammatory drugs (NSAIDs)) are used for the prevention and relief of the inflammatory process. Along with the fact that corticosteroids are the «gold standard» treatment of inflammation in ophthalmology, they have a number of serious side effects such as increasing of intraocular pressure and the risk of developing glaucoma, cataracts, activation of bacterial, viral infection and herpes. The positive effects of NSAIDs in comparison with corticosteroids are stable intraocular pressure (IOP), analgesic effect and reduce the risk of secondary infection. The three classes of NSADs are currently used in ophthalmology. They are phenylacetic acid (diclofenac and bromfenac nepafenak), indole acetic acid (indomethacin) and geteroariluksunoy acid (ketorolac). The last synthesized NSAIDs for ophthalmology are amfenac and bromfenac. Bromfenac is effective for the relief of the inflammatory symptoms of and fully complies with the requirements for the ideal anti-inflammatory drugs such as good a penetration ability, creating a sufficient concentration inside the eye, the activity of cyclooxygenase, inhibiting the progress of macular edema, a good analgesic effect, minimal toxicity, comfort of use patients. Bromfenac is the only nonsteroidal antiinflammatory drugs, which is applied once a day and has a pronounced anti-inflammatory action.